Zakat as an Instrument of Eradicating Poverty (Indonesian Case) - Mohamad Anton Athoillah (UIN Sunan Gunung Djati Bandung, 2013)
This paper describes more clearly about the charity as an instrument of poverty alleviation. Said to be more pronounced because zakat is not only described from the aspect of Islamic law, but also from the aspect of Islamic Economics. Starting from the idea of a content analysis of two professors of Economic Development, Prahalad and Yuyun Wirasasmita, this paper reveals the fundamental aspects of the causes of poverty, namely culture, alienation and exploitation. In this paper, the charity manages to pack in a comprehensive manner to a complementary instrument, whether Islamic law, and even Islamic Economics. Among the novelties in this paper is a substantive interpretation of zakat which is connected with the theory of economic development, compared with tax and economic-mathematical analysis to find a charity to further its position in the study of economics. As for other things that were outlined in this paper is the normative aspects of zakat, as where made explicit, as an instrument of poverty alleviation for various sectors, as seen from its usability goals.